C-Remor: UVC-Room Sterilization Mobile Robot - Ningsih, Prajna Paramitha Effendira Insan Adi; Winantyo, Rangga (Journal of Electronic Voltage and Application, 2023)
Mobile robots can be used in a variety of Internet of Things projects. The sterilization robot is created in the form of a mobile robot by combining two microcontrollers. The Arduino Uno microcontroller provides a sensor acquisition device, while the ESP32-cam provides the actuator controller, which is linked to the Wi-Fi network displayed on the web server. The millis function has been used in the Arduino module programming process because it requires doing tasks at the same time. This modeling system has an accuracy of about 80% for Arduino module settings as sensor controllers and 80%-86% for ESP32-cam modules as user interfaces and actuator controllers. This is due to the sensor’s limited range and the Wi-Fi network used.